An examination of acculturation, ethnic identity, discrimination, and offending among U.S. Hispanic persons - Centelles, Vanessa (Criminal justice and behavior, 2023)
Although racial and ethnic differences in offending are well-established, the processes associated with those relationships for U.S. Hispanic persons are less known. Using a nationally representative sample of U.S. Hispanic adults, the current study contributes to the literature by focusing on three factors thought to be particularly salient for understanding offending among U.S. Hispanic persons: acculturation, ethnic identity, and discrimination. We examine the association of each of these with offending, as well as the potential interactions between them. We found that acculturation and discrimination were positively associated with violent and nonviolent offending and ethnic identity was associated with nonviolent offending. For nonviolent offending, there was a positive interaction between acculturation and discrimination, such that experiences of discrimination intensified the relationship between acculturation and nonviolent offending. Findings are discussed in relation to both individual and contextual factors that are associated with health and behavioral outcomes, including offending, for U.S. Hispanic persons.